A theoretical model for prediction of shear strength in reinforced concrete beams with discrete or continuous transverse reinforcement. (October 2022) - Zakerinejad, Mohammad; Soltani, Masoud
Abstract: Shear failure of reinforced concrete falls into the category of brittle and undesirable failure modes and has caused catastrophic incidents in structures and infrastructures throughout the world. The complicated nature of shear behavior in reinforced concrete has made it a disputed subject in structural engineering. Via a parametric study on the shear capacity of reinforced concrete panels based on the Local Stress Field Approach (LSFA) and the assumption of a thorough and compatible physical model, an efficient method for predicting shear capacity in reinforced concrete members is introduced in this study. Using a large and strong experimental database of reinforced concrete slender beams failed in shear, along with a database of reinforced concrete panels that experienced failure under in-plane loads, it is shown that the proposed method is a reliable, simple, and easy to use approach that has high accuracy in calculation of shear capacity of slender reinforced or prestressed concrete beams, in comparison with existing reputed methods and leads to safe and economical results. Furthermore, studies show that Rectangular Spiral Reinforcement (RSR) can improve reinforced concrete beams' shear behavior and shear capacity. However, existing shear design provisions, even the most advanced ones, cannot predict this improvement in capacity. It is shown that the proposed relationships are able to predict the enhancement in the shear capacity of reinforced concrete beams with RSR.